Constructing Bayesian new group chain acceptance sampling plans (BNGChSP-1) using tangent angle for probabilistic quality region (PQR) and limiting quality region (LQR) - Mohd Azri Pawan Teh,; Nazrina Aziz,; Waqar Hafeez,; Md Amin Ullah Sheikh,; Aiman Fikri Jamaludin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article develops Bayesian new group chain acceptance sampling plans (BNGChSP-1) using the tangent angle for two distinct regions, namely the probabilistic quality region (PQR) and the limiting quality region (LQR). The BNGChSP-1, which makes use of past knowledge about the process variation, can be used as an alternative to traditional plans for evaluating the processes that generate the lots. The angle for both regions is calculated by using the tangent, and the region with a smaller angle resembles the ideal operating characteristics (OC) curve better than the region with a bigger angle. The finding shows that the PQR generates a smaller angle than the LQR, suggesting that the PQR more closely resembles the ideal OC curve compared to the LQR. The smaller angle indicates that the PQR offers greater protection to both producers and consumers than the LQR.